Improved analysis for impact response prediction of reinforced concrete structures considering stress wave propagation and time dependent shape function - Cui, Liuliang; Zhang, Xihong; Hao, Hong (Elsevier, 2023)
In the design of reinforced concrete (RC) structures subjected to impulsive loading, usually an equivalent Single-Degree-of-Freedom (SDOF) system is derived based on a constant deflection shape assumption corresponding to static-loading condition. It is commonly known that this idealized assumption may not necessarily lead to accurate predictions of structural responses. This paper presents an improved analytical approach to predict the dynamic response of RC beams with consideration of stress wave propagation effect in the beam in the initial stage upon impact load application, and time-dependent shape function for SDOF analysis. The response of a structural component is divided into two phases: local response phase which is calculated using governing equations of stress wave propagations; and global response phase analyzed using the equivalent SDOF systems with considerations of time-dependent deformation shapes. Laboratory drop-weight impact tests are performed on RC beams, which are used to validate the developed method. Further validation is carried out against existing testing results by other researchers, demonstrating the proposed approach offers more accurate predictions of RC beam responses under impact loading compared to the conventional SDOF method.